Práctica del rap estilo libre en Argentina: antecedentes históricos (2021)
Improvisation as a subgenre of rap reached its peak during the 21st century, achieving that many groups of young people organized themselves cooperatively, on the one hand, and that the market incorporated it by supporting it with advertisements and organizing events at an international level, on the other hand. In this article, I analyze the appropriation of the practice of improvisation or freestyle by rappers in Argentina and the emergence of improvisation battles organized in public and self-managed spaces, from a historical perspective. As a spatial and temporal framework, I will take the city of Buenos Aires and its suburbs, since the arrival of rap to the present day, to observe the social and aesthetic issues under the focus of Oral History. To do so, I analyze the practice of improvisation through the temporal classification of three generations proposed by the Universidad Nacional Arturo Jauretche: the old school, the first generation, and rappers 2.0.